The Influence of Reproductive Health Education on Adolescents' Knowledge Regarding Sexual Behavior in Schools - Siti Rukmana; Yeviza Puspitasari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Adolescent reproductive health issues have become an increasing public health concern. Insufficient knowledge of reproductive and sexual health has contributed to a higher proportion of adolescents engaging in premarital sexual behavior, highlighting the need for comprehensive and evidence-based reproductive health education. Reproductive health education has emerged as one of the primary health promotion interventions aimed at breaking the cycle of misconceptions surrounding reproductive health The aim of this research is determine the impact of reproductive health education on the level of adolescent knowledge regarding sexual behavior in schools. Scoping Review by Arksey and O'Malley. Date based are Pubmed, Scopus, Science Direct and Google Scholar 15 articles were reviewed by JBI. The results revealed All of the studies included in this review reported statistically significant improvements in adolescents' knowledge, with p-values ≤ 0.05 following reproductive health education .The most substantial gains in knowledge were observed in the domains of reproductive anatomy and physiology, prevention of unintended pregnancy, and awareness of the risks and prevention of sexually transmitted infections, including HIV. Furthermore, the synthesis of the evidence revealed a clear shift in educational approaches, moving away from traditional lecture-based methods toward the adoption of interactive digital media, gamification, and edutainment-based interventions, which have demonstrated greater effectiveness in enhancing students' engagement, comprehension, and knowledge retention.